Gambaran Kepuasan Pasien Terhadap Penggunaan Anjungan Pendaftaran Mandiri (APM) Di RSU Pakuwon Sumedang Tahun 2022 - Shiila Nika Adiffa; Imas Masturoh (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
APM is a self registration machine in which contains a touchscreen display, barcode scanner, printer or other additional tools. There are several problems related to the use of APM at Pakuwon Hospital, one of them is the queue number that can’t be printed due to the error of SIMRS network. This situation makes the process of service obtained by patients hampered. The quality of service provided by the hospital to the patient can lead to a sense of patient satisfaction. Patient satisfaction must always be considered because it relates to the subjectivity value to the quality of services provided. The purpose of this was to determine the level of satisfaction of patients using APM at Pakuwon Sumedang General Hospital. Method used in this study is quantitative with descriptive resejiarch design. The measurement of satisfaction using the End User Computing Satisfaction (EUCS) which determines from 5 dimensions. The population were 72,364 patients and the samples of this study were 110 patients. Data collection techniques using a questionnaire. Data analysis using a criterion score. The characteristics of the respondents contained in this stud based on age, education, occupation and membership status. The level of satisfaction obtained based on the content aspect is 89.22%, the accuracy aspect is 87.60%, the format aspect is 88.37%, the timeliness aspect is 86.98%, the ease of use aspect is 88.50% and overall patient satisfaction is 84.30%.